Perancangan Sistem Informasi Pendaftaran Pasien Rawat Jalan Menggunakan Visual Studio 2010 Di RSUD Al-Ihsan - Aillin Elizabeth Joel; Yunengsih, Yuyun; Abdussalaam, Falaah (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Registration is the initial process of the entire medical recording process that will be carried out on patients in the implementation of health services to patients. Registration is one of the very important initial processes. This study aims to determine the design of the outpatient patient registration information system using Microsoft Visual Studio 2010 at RSUD Al-Ihsan so that the outpatient patient registration process can be well-integrated and efficient in terms of patient service time and also make it easier for officers to register patients. The research method used in this study is a qualitative method with a descriptive approach. The technique used to collect data was through direct observation, interviews with medical record officers, and also a literature review of previous studies. The problem that occurred in the hospital was when patients registered for outpatient services, the patient's name did not appear in the system. To overcome this problem, this design was made using the System Development Life Cycle (SDLC) development method through the stages of needs analysis, design, implementation, and testing assisted by the creation of flowmap designs, Context Diagrams, Data Flow Diagrams, and Entity Relationship Diagrams, which were then implemented using Microsoft Visual Studio 2010 as a programming language using the Microsoft Access database so that the data that has been inputted can be saved so that the names of patients who have registered for outpatient services can appear. The results of the system design that have been made and tested using Black Box testing show that the system functions as intended. In conclusion, the information system design can help and facilitate registration officers in serving patients at the outpatient patient acceptance site effectively and efficiently.